NATURAL RESOURCE POTENTIAL IN ROSWAR AND RUMBERPON DISTRICTS, TELUK WONDAMA REGENCY, WEST PAPUA PROVINCE - Eko Nugroho, Nandra; Mughni Pratiwi, Ira; Deliana Siregar, Anggi (JOURNAL ONLINE OF PHYSICS, 2024)
Indonesia complex tectonic order to bring the positive impact of abundant natural resources. However, the distribution of potential natural resources with economic value is not evenly distributed. Teluk Wondama Regency has potential of minerals/mining, including limestone and quartz sand. The mining sector is one of the secondary sectors in Teluk Wondama Regency which contributes to Teluk Wondama gross regional domestic product per capita (GDP). Mining, processing, and industry activity relies on mineral exploration. So it is necessary to identify the potential and feasibility in the mining sector through a qualitative approach and descriptive-analytic. The Roswar and Rumberpon districts have the potential for natural resources in the form of limestone quarries and quartz sand as well as geothermal manifestations in the form of hot springs. However, technically (quantity and quality) and environmentally, the commodities of limestone and quartz sand are not exploitation profitable. Meanwhile, the hot springs are directed as a tourist destination.